Studi Penerapan Kontrak Long Segment untuk Preservasi Jalan di Kabupaten Sorong Papua Barat - Jekson Paulus Iek (Universitas Muhammadiyah Surabaya, 2019)
AbstractThis study aims to determine the readiness of service users, contractors and supervisor consultants on performance indicators in implementing long segment contracts for road preservation in Sorong Regency, and compare whether there are differences in perceptions between service users, contractors and supervisor consultants on these performance indicators in implementing long segment contracts. This study uses statistical analysis methods with the calculation of the mean value, calculation of standard deviation, and Analysis of Variance with the help of Microsoft Exel and SPSS version 20 computer programs in data processing. The results of data processing show that for the level of readiness according to the perception of service users, from the five indicators there are three indicators that are less ready, namely indicators of service provider readiness, payment system indicators and regulatory aspects indicators. For the level of readiness according to the perceptions of the contractor, of the five indicators there are four indicators that are less ready, namely indicators of service provider readiness, monitoring system indicators, payment system indicators and regulatory aspects indicators. And for the level of readiness according to the perceptions of the supervisor consultant, from the five indicators there are three indicators that are less ready, namely indicators of service provider readiness, payment system indicators and regulatory aspects indicators. There is also a perception perception between service users, contractors and supervisor consultants on service user readiness indicators, service provider readiness indicators, supervisory system indicators, payment system indicators and regulatory aspect indicators. Therefore, before implementing a long segment contract for road preservation in Sorong Regency, improvements must be made to indicators that are not ready, so that the standard performance indicators in long segment contracts can be implemented properly. Keywords: Implementation, Long Segment contract, Road preservation AbstrakPenelitian ini bertujuan untuk mengetahui kesiapan pengguna jasa, kontraktor dan konsultan pengawas terhadap indikator – indikator kinerja dalam penerapan kontrak long segment untuk preservasi jalan di Kabupaten Sorong, dan membandingkan apakah ada perbedaan persepsi antara pengguna jasa, kontraktor dan konsultan pengawas terhadap indikator – indikator kinerja tersebut dalam penerapan kontrak long segment. Penelitian ini menggunakan metode analisis statistik dengan perhitungan nilai mean, perhitungan standar deviasi, dan Analysis of Varians dengan bantuan program komputer Microsoft Exel dan SPSS versi 20 dalam pengolahan data. Hasil pegolahan data diketahui bahwa untuk tingkat kesiapan menurut persepsi pengguna jasa, dari lima indikator yang ada terdapat tiga indikator yang kurang siap yaitu indikator kesiapan penyedia jasa, indikator sistem pembayaran dan indikator aspek regulasi. Untuk tingkat kesiapan menurut persepsi kontraktor, dari lima indikator yang ada terdapat empat indikator yang kurang siap yaitu indikator kesiapan penyedia jasa, indikator sistem pengawasan, indikator sistem pembayaran dan indikator aspek regulasi. Dan untuk tingkat kesiapan menurut persepsi konsultan pengawas, dari lima indikator yang ada terdapat tiga indikator yang kurang siap yaitu indikator kesiapan penyedia jasa, indikator sistem pembayaran dan indikator aspek regulasi. Terdapat juga ada perberdaan persepsi antara pengguna jasa, kontraktor dan konsultan pengawas terhadap indikator kesiapan pengguna jasa, indikator kesiapan penyedia jasa, indikator sistem pengawasan, indikator sistem pembayaran dan indikator aspek regulasi. Oleh karena itu sebelum menerapkan kontrak long segment untuk preservasi jalan di Kabupaten Sorong, maka harus dilakukan pembenahan terhadap indikator – indikator yang kurang siap, sehingga untuk mencapai standar indikator kinerja dalam kontrak long segment bisa diterapkan dengan baik. Kata Kunci: Penerapan, Kontrak Long Segment, Preservasi Jalan